The Impact of Gender Diversity and Female Director's Characteristics on Firm Performance - Ai, Shufan (2019)
The impact of board gender diversity has been a controversial and much disputed subject within the field of corporate performance where a great number of studies have attempted to discover their relationship, but have not reached a unified conclusion. The purpose of this paper is to explore whether there is a relationship between female directors and their education political background of female directors on the boards of 86 Chinese companies in food and beverage industry and company performance. Data from 2013-2017 instead of 2018 was used because the information for 2018 has not been updated in the database completely and was difficult to obtain. This data was achieved from the RESSET and CSMAR databases, including ROA, ROE, as a dependent variable, and the percentage and a dummy variable for the women on the boards, and the educational and political background of female directors selected as independent variables. In addition to these mentioned factors, this paper also uses board size, company size and leverage as control variables, which were also considered to affect company performance in previous studies. To test this relationship, the STATA software was employed to perform OLS regression analysis. Unlike some previous studies, this piece of research finds a negative correlation between board gender diversity and company performance. At the same time, the educational background has proven to be unrelated to company performance, and the political background of female directors can positively influence company performance.